Validation of the AgraStrip® Gluten G12 Test Kit. (27th November 2019) - Radcliffe, Scott; Sutzko, Meredith; Jiang, Zheng; Freitag, Denise; Swoboda, Christy; Frank, Lukas; Rogers, Adrian
Abstract: Romer Labs ®, Inc. developed an immunochromatographic lateral flow assay for the qualitative detection of gluten in raw ingredients, processed foods, finished food products, and environmental surfaces, using the G12 antibody developed by Belén Morón. The G12 antibody targets a 33-mer peptide which is resistant to enzymatic digestion and heat denaturation, as well as being the fragment of the gliadin protein to which celiac disease sufferers react, making it a reliable analytical marker. This study was performed to validate the AgraStrip ® Gluten G12 assay method under the guidance of the AOAC Performance Tested Methods SM (PTM) program against AOAC Official Method of Analysis SM 2012.01 in rice flour, bread, cookie, ice cream, and chocolate matrixes spiked with either purified gliadin or wheat gluten standard at 0, 3, 8, 15, and 25 ppm concentrations and tested at the 5, 10, and 20 ppm assay thresholds, as well as on environmental surfaces. Stability, robustness, variation, and lot consistency studies were performed by spiking wheat gluten into a rice flour matrix at 0 and 15 ppm concentrations. The AgraStrip Gluten G12 assay was rigorously evaluated during this study and demonstrates its suitability as an AOAC PTM-certified gluten detection method.